Respon Perokok Remaja Terhadap Peringatan Kesehatan Bergambar di Bungkus Rokok - Nurahmi, Leni; Damayanti, Rita (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background. Smoking is risk factor of chronic and deadly diseases in the world. In 2014, 80% of 5.8 billion smokers in the world started smoking at 17.6 years old. Pictorial health warning on cigarette pack was implemented since 24 June 2014 in Indonesia to protect teenagers from smoking. Objective. This study aimed to assess teenage smokers’ responses toward pictorial health warning on cigarette pack in Depok City. Method. This cross-sectional study used a questionnaire from the Center for Health Research Universitas Indoonesia. Result. We found differences in fear, severity, response efficacy and intention. We found no differences in susceptibility, self efficacy, acceptance and ignorance to pictorial health warning.